Factors associated with men involvement in child nutrition in health center area of Burundi - Manirakiza, Boniface; Munezero, Florence; Harimenshi, Deo (International Journal Of Community Medicine And Public Health, 2024)
Background: Men play a central role in decision making regarding women’s and children’s health, their involvement in child nutrition has been proven to be essential in the prevention of child undernutrition. In Burundi, nutrition interventions have been introduced to strengthen mothers’ knowledge on infant feeding, but no interventions are targeting men specifically. The objective of this study was to analyze the factors of men involvement in child nutrition. Methods: A cross-sectional analytical study was carried out from July 2023 up March 2024 in health centers of Vumbi health district in Burundi. The study population consisted of 231 men with children aged 6-23 months. A questionnaire downloaded in Kobocollect application was used during data collection and the analysis were performed using Stata 15. Results: The level of men involvement in child nutrition was 53.68% in the area. The men education level (OR=2.54; CI95%: [1.36-4.75]), men participation in nutrition sessions facilitated by the CHWs (OR=3.29; CI95%: [1.82-5.96]), men knowledge in terms of their involvement in child nutrition (OR=2.00; CI95%: [1.12-3.56]), and women accompaniment to health services (OR=2.30; CI95%: [1.18-4.46]) all with p<0.05 were statistically associated with men involvement in child nutrition. Conclusions: The men involvement in children nutrition for Muramba health center is low, which demonstrates a flaw in child nutrition with the consequent high rate of malnourished children in the locality.